AIDS and ARC: Pastoral issues in the hospital setting - Phillips, Jennifer M. (Journal of religion and health, 1988)
Eight areas of fear for persons with Acquired Immune Deficiency Syndrome and its related conditions are explored: change and stress, uncertainty and the unknown, waiting, the fear of symptoms, fear of contagion, abandonment, dependency and spiritual distress. Some particular issues of sub-populations with HIV infection are detailed. Suggestions for helpful pastoral responses to the common concerns and anxieties of patients and their loved ones are offered.